School inclusion: analyzing the establishment and organization of a special needs education service in a brazilian municipality - Dall'Acqua, Maria Júlia Canazza [UNESP]; Carneiro, Relma Urel Carbone [UNESP]; Zaniolo, Leandro Osni [UNESP] (Scientific Research Publishing, 2014)
The present research integrates a network of studies called National Monitoring Center for Special Education (NMCSE) which studies the Multi-purpose Feature Rooms (MFRs) in regular schools. We aim to investigate whether the service offered by such rooms, maintained by the Department of Education of the Municipality of Araraquara, in São Paulo State, Brazil, is being successful at supporting the education of children and youth with special needs, pervasive developmental disorders and high skilled/gifted individuals. We have also investigated the limits and possibilities of such rooms concerning the set of services offered to their participants. In order to conduct the present research, we have performed: an interview with the Special Education Program manager from the abovementioned Department of Education; and the analysis of a Training Program that MFRs teachers must take. The training program consists of ten morning and afternoon shift meetings. The analyzed data leads us to conclude that the policy of implementation of MFRs, even in this relatively restricted universe is seen from different perspectives. Some interpretations are still permeated by the clinical model, considering individual action. The challenges observed in the classrooms show that the cooperation among teachers still occur randomly and, among other difficulties raised by them, is the selection of the right placement methods to identify eligible students who will benefit from the Specialized Educational Service (SES). In addition, teaching evaluation was considered fragile, as well as the training and the general requirements demanded in order to achieve the expected results.
Keywords: Specialized Education Services; Inclusion; Public Policies